PERANAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENGAWASAN PENINGKATAN PENDAPATAN ASLI DESA (PAD) KABUPATEN SINJAI - Immawan Syahril; Abdul Wahid; Hasriani Hasriani (DEMOKRASI, 2022)
Abstract made in two languages namely Indonesian and English. Abstract consisting of one paragraph, the number of words between 75-200 words. Abstract should contain research background/purpose, methods, result and discussion and conclusions. Abstract does not contain a description of mathematical and statical language, it does not contain a quoe, do not use abbreviations